A simple synthesis of Co3O4@CNT to boost electrochemical nitrogen fixation. (20th January 2021) - Wen, Juan; Chang, Huhu; Huang, Ting; Hossain, Masud; Liu, Zaichun; Sun, Haodong; Zhu, Yusong; Chen, Yuhui; Huang, Qinghong; Wu, Yuping
Highlights: The synergistic effect of Co3 O4 and CNT improves individual performance. The large specific surface area of Co3 O4 @CNT provides sufficient sites for physical adsorbing of N2 . Co3 O4 is evenly coated on CNT to optimize the electronic conductivity of Co3 O4 itself and improve the reaction kinetics. Abstract: The synthesis of ammonia in industrial-scale mainly depends on Haber-Bosch process, which entails huge energy consumption and massive CO2 emission. Electrocatalytic nitrogen-to-ammonia is a promising alternative, which could be powered by renewable energy source. However, the development of proper catalysts with good yield, superior stability, and excellent selectivity is one of the most challenges for electrochemical reduction of nitrogen. Here, a cost-efficient electrocatalytic material, Co3 O4 coated on CNT, was reported as an electrocatalytic nitrogen reduction reaction catalyst to generate NH3 . Applying CNT as an excellent substrate for growing Co3 O4 could effectively improve the electronic conduction properties and boost N2 adsorption. This catalyst attains a favorable NH3 yield as 27. 16  ± 2.22 µg h −1 mgcat. −1 at −0.49 V vs. RHE in 0.1 M Na2 SO4 solution under ambient conditions. It also shows strong electrochemical durability and excellent selectivity. Graphical abstract: Image, graphical abstract